2005
DOI: 10.1111/j.1365-2435.2005.01051.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of visual and tactile stimulation on growth and metamorphosis in anuran larvae

Abstract: Summary1. Sensory modalities that allow tadpoles to assess their environment, and subsequently mediate their development, are not well understood. 2. By putting clay model tadpoles into the tanks with live tadpoles we have enhanced tactile and visual stimuli for tadpoles of three species ( Rana sylvatica , Bufo americanus and Xenopus laevis ) in a controlled fashion. The goal was to determine whether visual and tactile cues in the absence of chemical signals influenced tadpole growth and development. 3. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 54 publications
3
31
0
Order By: Relevance
“…Regardless of the mechanism, the results from these two studies highlight that environmental conditions influence both somatic and reproductive growth and development, apparently in a sex-specific manner. In addition, our finding that animals housed together, developed and grew faster than those housed individually are consistent with recent studies showing that tadpoles experiencing tactile, chemical, and visual stimuli from other tadpoles tend to develop and grow more rapidly than those reared in isolation (Rot-Nikcevic et al, 2005.…”
Section: Discussionsupporting
confidence: 92%
“…Regardless of the mechanism, the results from these two studies highlight that environmental conditions influence both somatic and reproductive growth and development, apparently in a sex-specific manner. In addition, our finding that animals housed together, developed and grew faster than those housed individually are consistent with recent studies showing that tadpoles experiencing tactile, chemical, and visual stimuli from other tadpoles tend to develop and grow more rapidly than those reared in isolation (Rot-Nikcevic et al, 2005.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, they were able to reverse growth inhibition by treating tadpoles with metyrapone, an inhibitor of corticoid synthesis. Recent results suggest that Rana sylvatica tadpoles respond in a similar fashion, with elevated corticosterone at simulated high densities (40 tadpoles/10 L) in the laboratory (Rot-Nikcevic et al 2005). These studies provide strong support for a role of corticosterone in regulating responses to density.…”
Section: Discussionmentioning
confidence: 75%
“…Previous laboratory studies have demonstrated that high population density (i.e., 10 tadpoles/L) can increase corticosterone levels in tadpoles (Hayes 1997;Glennemeier and Denver 2002b). Consequently, Glennemeier and Denver (2002b) suggested that corticosterone secretion may be the physiological mechanism by which high density reduces growth in larval anurans, and recent work on the sensory cues used by tadpoles has also found support for that hypothesis (Rot-Nikcevic et al 2005).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…This suggests that tadpoles can integrate multiple sources of information to generate a phenotypic response to the environment. Tadpoles are known to have adaptive phenotypic responses to a wide range of environmental cues, including pond drying (Denver 1997;Newman 1989), limited food resources (Alford and Harris 1988;Hentschel 1999;Travis 1984), presence of predators (Relyea 2001a;Van Buskirk 2002) or competitors (e.g., Pfennig and Murphy 2002;Relyea 2002), and crowding (Rot-Nikcevic et al 2005, 2006. However, the eVect of multiple cues that may contain diVerent information about the environment on tadpole phenotype is not well understood.…”
Section: Contrasting Coeycients and Exponentsmentioning
confidence: 98%